ARTI PENTING PENDIDIKAN MITIGASI BENCANA DALAM MENGURANGI RESIKO BENCANA - Dradjat Suhardjo (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Significance of Disaster Mitigation Education in Reducing Disaster Risks. More than 60% of the areas in our country are threatened by earthquakes, besides tsunamis, volcano eruptions, floods, landslides, forest fires, and biodiversity degradation. This article focuses on the mitigation of such natural disasters, especially earthquakes, tsunamis, and volcanic eruption, through the Disaster Risk Reduction (DRR) program. Up to now, there has been no technology capable of accurately predicting when earthquakes and tsunamis will occur. One effective action to anticipate them is through sustainable education and training programs for children, youths, and adults. The goals of the programs are to provide them with self-help to save their lives, encourage them to participate in the programs, and make the adults initiators in the disaster management. Thus the curriculum should be designed for learning and training to implement the DRR program and should include local wisdom. Keywords: education, mitigation, local wisdom